Framework of SDG leadership among SMEs in South Asian nations-using Interpretive Structural Modelling - Priti Bakhshi; Reena Agrawal; Suhan Mendon; Ramona Birau; Iuliana Carmen Bărbăcioru (Cogent Business & Management, 2023)
This research paper investigates the enablers of Sustainable Development Goals (SDG) leadership among Small and Medium Enterprises (SMEs) in South Asian nations using Interpretive Structural Modelling (ISM). The study focuses on identifying the factors that facilitate SDG leadership in SMEs, including shared vision, long-term perspective, co-creation, shared responsibility, empowering people, eco-centric values, creativity and innovation, bonding and trust, knowledge sharing, strategic adaption, and progressive culture. The research findings show that these factors are interrelated, and their integration can help SMEs to achieve sustainable development and become SDG leaders in their respective industries. The study contributes to the existing literature by providing insights into the enablers of SDG leadership among SMEs in South Asian nations and proposing a framework for their successful implementation. The proposed framework can be used as a guide for policymakers, managers, and entrepreneurs to promote sustainable development in their organizations and the region.
Keywords: 650; co-creation; creativity; emerging economy; innovation; leadership; organization management; shared vision; Small and Medium Enterprises (SMEs); sustainable development; Sustainable Development Goals (SDGs)